2015
DOI: 10.1007/s10815-015-0515-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased body mass index negatively impacts blastocyst formation rate in normal responders undergoing in vitro fertilization

Abstract: Purpose The aim of this study is to investigate the effect of female BMI and metabolic dysfunction on blastocyst formation rate. Methods This was a retrospective cohort study that was performed in an academic center for reproductive medicine. Patients who were normal weight, overweight with metabolic dysfunction, or obese who had ≥6 oocytes retrieved in a fresh IVF cycle were included in the study. The blastocyst formation rate was calculated from the number of ≥5 cell embryos on day 3 observed in culture unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 31 publications
2
38
3
3
Order By: Relevance
“…A significantly lower number of mature oocytes, as well as oocytes that were reduced in diameter, were observed in ovarian aspirations in IVF cycles among obese women compared with women of a normal weight . Embryos formed from ova of overweight and obese women also exhibited a lower potential for development after IVF, as well as a lower rate of blastocyst formation …”
Section: Discussionmentioning
confidence: 95%
“…A significantly lower number of mature oocytes, as well as oocytes that were reduced in diameter, were observed in ovarian aspirations in IVF cycles among obese women compared with women of a normal weight . Embryos formed from ova of overweight and obese women also exhibited a lower potential for development after IVF, as well as a lower rate of blastocyst formation …”
Section: Discussionmentioning
confidence: 95%
“…Data from the literature are not consensual regarding the effect of obesity and its severity on live birth rate. Indeed, some studies did not find any deleterious effect of BMI, with no significant difference in the live birth rate between normal-weight and overweight women [16,17], but also between normal-weight and obese women [7,18] and between BMI categories [19]. Likewise, Coyne et al showed that gestational carriers' BMI does not impair reproductive outcomes including live birth rate [20].…”
Section: Discussionmentioning
confidence: 99%
“…A s the obesity epidemic continues to plague the United States, numerous reports have been published and recommendations made regarding the negative impact of obesity on fertility (1), assisted reproductive technology (ART) effectiveness (2)(3)(4)(5)(6)(7)(8)(9), and pregnancy and obstetric outcomes (5,10). By contrast, limited and conflicting data exist on the impact of being underweight (body mass index [BMI] <18.5 kg/m 2 ), admittedly a less common problem, on fertility and the effectiveness of ART.…”
mentioning
confidence: 99%